Facebook jako narzędzie odwoływania się do ogólnokrajowych sporów politycznych przez lokalnych polityków – analiza na przykładzie samorządowców z miast na prawach powiatu z województwa śląskiego - Bąk, Aneta; Kubisz-Muła, Łukasz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
This article presents the findings of a study concerning the use of the social media platform, Facebook, by local politicians to express their opinion on national political disputes. The analysis covered entries published by local politicians from the Silesian municipal boroughs, on their accounts over a period of 16 months, from the day of the parliamentary elections in 2015. The study revealed, among other data, that the fact and frequency of publishing posts concerning political disputes in social media depends on whether the local politician is a councillor or a president of the municipality and whether he/she is a representative of a main political party or not. The analyses also showed that nearly 80% of entries on national political disputes have a different author than the person who publishes the posts, and local politicians merely share posts made available by other people.
Facebook as a tool for referring to national political disputes by local politicians. Analysis based on the example of local governments of Silesian municipal boroughs
Keywords: social media; Facebook; national political disputes; local politicians